Simulasi distribusi temperatur pada friction stir welding dengan tool pin silinder - Gesa Sukmawan; Dominicus Danardono; Bambang Kusharjanta (Jurnal Teknik Mesin Indonesia, 2016)
In friction stir welding, it is very important to understand temperature distribution. A three dimensional model temperature distribution during friction stir weldingof the nylon 6 using cylindrical and tapered pin has been simulated using finite element method. A steady state finite Element analysis are performed to obtain the temperature distribution in the welded nylon 6 plate during the welding operation. Heat source from the tool shoulder and the tool pin are set up 80% of the melting point nylon 6. The model has been implemented and solved using ANSYS CFX software. The result showed that peak temperature are higher on the advancing side than the retreating side at the beginning and middle position of friction stir welding process using cylindrical and tapered pin. While the final position of the friction stir welding process with cylindrical and tapered pin, the peak temperature at the retreating side was higher than the advancing side. For overall position of the friction stir welding process with cylindrical and tapered pin, temperature distribution behind the pin was higher than the front pin.